2020
DOI: 10.1007/s10995-020-02987-3
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Patterns, Physical Activity, and Socioeconomic Associations in a Midwestern Cohort of Healthy Reproductive-Age Women

Abstract: Objective: To characterize dietary patterns and physical activity in a diverse cohort of Midwestern reproductive-age women and to determine associations between these lifestyle factors, socioeconomic factors, and obesity. Methods:In this cross-sectional study, 185 women completed validated food frequency and physical activity questionnaires. Dietary patterns were identified through principal component analysis. Sociodemographic characteristics associated with dietary pattern adherence and physical activity par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…The moderate-high level of physical activity we observed in about 70% of the women enrolled appears supported by similar healthy lifestyle habits described by Bedrick et al [48] in a cohort of women of childbearing age.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The moderate-high level of physical activity we observed in about 70% of the women enrolled appears supported by similar healthy lifestyle habits described by Bedrick et al [48] in a cohort of women of childbearing age.…”
Section: Discussionsupporting
confidence: 90%
“…The adapted version of the Turconi et al questionnaire [38] and the IPAQ questionnaire [41] allowed us to estimate a prevalence of rather healthy lifestyle habits for more than 60% of the women we enrolled. The study of Bedrick et al [48] confirmed the presence of two dominant dietary patterns in a cohort of midwestern women of reproductive age. In particular, according to a food frequency assessment, one pattern was defined as healthier and the other one less healthy, with prevalence values similar to those we observed in the present research and falling in the range of previous studies [48].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…A key limitation was the exclusion of physical activity as a confounder in our models, especially when previous studies [ 54 , 55 ] show that physical activity reduces the probability of obesity. Energy intake was also not adjusted for; however, energy adjustment does not reveal any significant results [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this cross-sectional study, reproductive age women were recruited from the St. Louis, Missouri metropolitan area for participation in the LORe study—lifestyle and reproductive outcomes—between May 2014 and May 2018 [ 17 ]. Briefly, women 18 to 44 years of age with regular menstrual cycles were eligible for the study.…”
Section: Methodsmentioning
confidence: 99%